2019
DOI: 10.1111/apt.15245
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death protein‐1 (PD‐1)‐targeted immunotherapy in advanced hepatocellular carcinoma: efficacy and safety data from an international multicentre real‐world cohort

Abstract: Summary Background Programmed cell death protein‐1‐targeted immunotherapy has shown promising results in phase II studies of hepatocellular carcinoma. Aim To evaluate safety and efficacy of nivolumab and pembrolizumab in an international, multicentre, real‐world cohort of patients with advanced hepatocellular carcinoma. Methods Sixty‐five patients treated with nivolumab (n = 34) or pembrolizumab (n = 31) between July 10, 2015 and December 31, 2018 (data cut‐off) across six centres in Austria and Germany were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
120
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 120 publications
(137 citation statements)
references
References 41 publications
14
120
1
2
Order By: Relevance
“…Real life data on nivolumab in HCC provided by Gomes da Fonseca et al at the 2019 International Liver Congress showed a safety profile consistent with clinical trials, with 42.9% of patients presenting adverse events, and a median overall survival in the patients receiving the drug as a second‐line treatment of 28.8 months since start of first line. Scheiner et al reported a similar rate of adverse events and a median overall survival of 11.0 months in a cohort of advanced HCC treated with nivolumab or pembrolizumab.…”
Section: Checkpoint Inhibitors In Hccmentioning
confidence: 80%
“…Real life data on nivolumab in HCC provided by Gomes da Fonseca et al at the 2019 International Liver Congress showed a safety profile consistent with clinical trials, with 42.9% of patients presenting adverse events, and a median overall survival in the patients receiving the drug as a second‐line treatment of 28.8 months since start of first line. Scheiner et al reported a similar rate of adverse events and a median overall survival of 11.0 months in a cohort of advanced HCC treated with nivolumab or pembrolizumab.…”
Section: Checkpoint Inhibitors In Hccmentioning
confidence: 80%
“…In a study investigating sorafenib for advanced HCC, patients with Child-Pugh B cirrhosis had similar rates of adverse events and shorter overall survival times than those with class A. 2,3 Adverse events among patients with Child-Pugh class C (n = 5) were not reported. A meta-analysis found that 14% of patients who received PD-1 and PD-L1 inhibitors developed at least one adverse event of grade 3 or higher severity.…”
mentioning
confidence: 99%
“…4,5 In the present study, 39% of patients experienced at least one adverse event, and the rate of hepatitis was 5%. 2 The second concern is about the treatment line of immunotherapy. No difference was observed in terms of efficacy or adverse events between patients with first/second-line and third/ fourth-line immunotherapy.…”
mentioning
confidence: 99%
See 2 more Smart Citations